A new record of bony fish prey for the genus Isistius (Chondrichthyes: Dalatiidae) in a coastal zone of southeastern Mexico - Armando T Wakida-Kusunoki; Vicente Anislado-Tolentino; Jorge I Rosales-Vásquez; Rodolfo Castro-Barbosa; Luis Fernando Del Moral-Flores (Novitates Caribaea, 2024)
The first report of bite wounds from cookiecutter shark in a specimen of cobia in the Southern Gulf of Mexico is described. The specimen was captured by artisanal fishery in the coastal zone of Tabasco, Mexico. It presented three bite wounds with 25 to 26 teeth marks per wound, major axis interval between 3.7 and 4.7 cm and all areas of less than 10 cm2. This is new record of a bony fish as prey of genus Isistius maybe of I. brasiliensis in coastal waters over the continental shelf, in the Southern Gulf of Mexico.